REPRESENTATION OF WOMEN’S PROFESIONALISM IN ANJI’S MUSIC VIDEO “ORANG YANG BERBEDA” - Sukra, Winda; Tiara, Andys; Setiawati, Titin (Universitas Muhammadiyah Jakarta, 2024)
The media has a strong influence in shaping people's perceptions and values, but unfortunately the messages conveyed are often not in favor of women. As a reflection of culture, the media often adopts, reinforces and even perpetuates the figure of women with negative connotations through certain roles and attributes that often undermine their abilities, especially in the public sector. Music videos are one form of media that often constructs women unfairly and undignified, to the point of being unprofessional on screen. This paper focuses on the controversial music video clip “Orang Yang Berbeda” by Anji, which is the locus of the author. The purpose of this writing is to try to uncover how the construction of women's professionalism is portrayed in the media. This writing is important to do as a form of effort in fighting for a fairer and more dignified portrayal and placement of women on screen, especially music videos. This writing seeks to contribute to a more positive and empowering representation of women in the media, which ultimately leads to gender equality. This paper will apply the concepts of Peter L. Berger and Thomas Luckmann's construction theory and De George's elements of professionalism to understand the reimagining of women's professionalism in music videos. This paper will use qualitative content analysis method, constructivism paradigm, and qualitative approach. The analysis will focus on the scenes and symbols in the music video. The results of the author's analysis of this music video show doubts about women's ability to work professionally. 4 out of 5 scenes illustrate how the two female roles, Yolla and Celline marginalize the aspects of professionalism stated by George, namely; professionalism must have strong integrity and not be easily tempted by material things or worldly pleasures and professionalism requires a harmony between thoughts and actions.